Differential involvement of the dorsal and lumbar spine in osteoporosis. Issue 9 (September 1992) - Bhambhani, M; Crisp, A J; Compston, J E
Abstract : The presence of normal bone density values in the lumbar spine is often assumed to exclude osteoporosis. Eleven cases are reported in which normal lumbar spine bone density and radiology were associated with one or more dorsal spine fractures; the diagnosis was postmenopausal osteoporosis in eight patients and corticosteroid induced osteoporosis in three. These findings suggest that spinal osteoporosis may sometimes be a focal disorder and emphasise the need for dorsal spine radiology in addition to bone densitometry in patients with strong risk factors for osteoporosis or with clinical evidence of the dorsal spine being affected.